Meningkatkan Prestasi Pembelajaran Mata Kuliah Dasar-Dasar Pemasaran Global Melalui Metode Pembelajaran Koorperatif Tipe Jigsaw - Wartini, Sri; Pramusinto, Hengky (Fakultas Ekonomi, Universitas Negeri Semarang, 2007)
Conceptual learning will be more qualified if it is supported by an appropriate and good learning method system. To improve the achievement of studentsÃ¢â‚¬â„¢ study result, it needs theÃ‚Â active studentsÃ¢â‚¬â„¢ involvementÃ‚Â who want to think critically toward the real condition in the field. This class action research has an objective to prove that cooperative method, jigsaw type can be implemented in the learning process on each subject whose conceptual type. The subject of this research was Management Department students, Regular Class, 5th semester with the sum was 67 students who got Basics of Management Subject. This research consisted of 3 cycles and found out that the increase of average for pre test and post test score in cycle 1 was 15%, cycle 2 was 20% and cycle 3 was 25%. Whereas the difference of Ã‚Â average increase among cycles were on cycle 1 to cycle 2 was 5%, cycle 2 to cycle 3 was 10%. The finding means there is an increase of achievement on each cycle was 5%. It is appropriate to the hypothesis. Thus, it proved that cooperative learning method , jigsaw type can be applied well to Global Marketing Subject and finally it can improve the studentsÃ¢â‚¬â„¢ learning achievement. Keywords: cooperative method, jigsaw type